Space, history and trauma in Doris Lessing's short fiction set in Europe. - Berio, Maria Eugenia (UMA Editorial, 2023)
The past two wars have left their mark on those who participated, witnessed, or had to live in an environment in which one or more traumatised veterans returned home carrying history on their bodies. Doris Lessing and her parents faced the horrors of war either vicariously or personally. Her literature has been tinted by wars either with an actual presence or hidden in the symbols, metaphors, and spaces used to construct her stories and novels. My doctoral thesis consists of literary research on the treatment of space in her short fiction set in Europe. The main objective of this thesis is to carry out an integral study about space in its tripartite division of physical, psychological, and socio-historical as well as an agent of traumatic representation in Doris Lessing's short fiction set in European places. The research is approached from a humanistic perspective supported by academics such as Henri Lefebvre, Michel Foucault, Yi-Fu Tuan, and Edward Soja who have delved into the study of space from different perspectives. Regarding trauma studies, I have consulted not only its pioneers in its inclusion in Cultural Studies such as Shoshana Felman, Dominick LaCapra, and Cathy Caruth but also other scholars who have broadened its scope of exploration. From the literary standpoint, I analyse space through the visions of authors like Laurie Vickroy, Geoffrey Hartman, and Roger Luckhurst, to mention just a few, who have extensively written on the topic of trauma and its effect on space. The scope of the analysis is limited to one novella and five short stories written in the aftermath of the past world war from Doris Lessing's book Stories published in 1978. The findings will demonstrate how Doris Lessing constructs her own Poetics of Space by foregrounding the traumatic spatial marks left by the wars.
Keywords: Lessing, Doris - Crítica e interpretación; Lessing, Doris - Temas, motivos; Literatura inglesa - S. XX - Tesis doctorales; Space; Doris Lessing; Trauma; War; History